Cost-of-illness of inflammatory bowel disease patients treated with anti-tumour necrosis factor: A French large single-centre experience. Issue 7 (August 2019) - Lawton, Jean; Achit, Hamza; Pouillon, Lieven; Boschetti, Emmanuelle; Demore, Béatrice; Matton, Thierry; Tournier, Charlène; Prodel, Martin; Peyrin-Biroulet, Laurent; Guillemin, Francis
Background: No study has evaluated the direct annual costs of inflammatory bowel disease patients treated with anti-tumour necrosis factor therapy. Objectives: The purpose of this study was to identify annual direct costs and main cost drivers of anti-tumour necrosis factor-treated inflammatory bowel disease patients. Methods: All inflammatory bowel disease patients treated with infliximab or adalimumab at Nancy University Hospital were consecutively screened for inclusion from November 2016–February 2017. Data about hospitalisation, surgery, medication, outpatient visits, investigations and transport over the previous 12 months were retrospectively collected. Results: A total of 108 patients ( n  = 83 Crohn's disease; n  = 25 ulcerative colitis) were included. The mean annual cost per patient was €15, 775 (standard deviation €7221), with no difference between Crohn's disease and ulcerative colitis ( p  = 0.2). The main cost driver was medication, which accounted for 84% of the total direct cost. Hospitalisation and surgery represented 11% and 2% of the direct costs. History of switch to another anti-tumour necrosis factor treatment was identified as the only independent predictor of greater direct costs in the multivariate analysis ( p  = 0.0018). Conclusions: In a French tertiary referral centre, direct costs of anti-tumour necrosis factor therapy-treated patients were mainly driven by medication, while hospitalisation and surgery represented only a minor part of the costs. There was no difference between Crohn's disease and ulcerative colitis patients.